"A Kangaroo and Bradman": Indian journalists' visit to Australia under the Colombo Plan, 1950–1957. (26th April 2019) - Sarwal, Amit
Abstract : Academic research on White Australia Policy and the Colombo Plan has spanned across the history of Asian migration, policy-making initiatives and Australia–India relations. But the role of popular transnational media images and stories that informs the sociocultural understanding of these relations has been under evaluated. In this article, using newspaper reports and notes of the tours, I highlight the building of popular perceptions under the Colombo Plan (1950–1957). By focusing on Indian journalists and editors, E. P. W. da Costa, J. N. Sahni, Frank Moraes, and Durga Das, this article contributes to the historiography of Australian–Indian relations. As these culture exchanges created a dialogue between the two countries that still influences the public opinion. The article concludes that journalists from both India and Australia sought to play a key role in image-making process and wanted a fresh start in relationship––politically, economically, sociologically and technologically.